INTEGRATING LOCAL WISDOM THROUGH PEUNAJOH-INDATU VIDEOS TO ENHANCE EFL STUDENTS’ SPEAKING SKILLS - Zuhra, Intan; Agustisa, Mutia; Darwis, Muhammad; Nurjannah, Nurjannah; Amalina, Zahria (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Numerous studies have investigated the use of videos as a medium for teaching English; however, there remains a significant gap in research on the utilization of local wisdom-based videos, particularly in the Indonesian context. This study examines students’ perceptions of employing Peunajoh-Indatu, a local wisdom-based procedure text video, as a tool to enhance their speaking skills. A quantitative research approach was adopted, with questionnaires serving as the primary data collection instrument. The study involved 25 final-year high school students from SMA Negeri 1 Kutablang. The findings reveal overwhelmingly positive responses from the students, with 80% agreeing that the use of local wisdom-based videos significantly motivated them to improve their speaking abilities. The integration of culturally relevant materials heightened their enthusiasm for learning and practicing speaking. Moreover, the accessibility of the videos allowed students to engage in independent learning by re-watching and practicing outside the classroom, further reinforcing their speaking competence and overall confidence.